Techniques Self-Regulated Learning To Improve Self-Regulated Learning and Students' Learning Independence in Online Learning Situations Covid The -19 - Muhamad Khoirudin; Eko Darminto (Indonesia Approach Education, 2021)
Ability Self-regulated learning and independent learning are needed for humans throughout their life. However, the students of SMP Sunan Ampel Porong do not yet have optimal learning independence. the study aims to improve self-regulated learning and increase the learning independence of Sunan Ampel Porong Junior High School students in online learning situations during the Covid-19, through the application of Self-Regulated Learning. This research uses experimental research, the method used is quasi-experimental research design with non-equivalent control group design. The research sample consisted of sixty-nine students of SMP Sunan Ampel Porong with two classes, the experimental class, and the control class. Data on self-regulated learning and learning independence of students were collected using observation, interviews, questionnaires, and document scrutiny techniques guidance instruments self-regulated learning. Furthermore, the data were analyzed quantitatively. Based on the post-test t-test of the ability Self Regulated Learning, it is known that the average learning outcomes of the experimental class are greater than that of the control class. From the table, it is known that the value of t count > t table. achievement scores' self-regulated learning in the experimental class and the control class. While the post-test t-test of learning independence of the experimental class is known to have an average learning outcome of the experimental class is greater than that of the control class. From the table, it is known that the value of t count > t table. It can be concluded that there are significant differences in the scores of students' independent learning outcomes in the experimental class and the control class.